2021
DOI: 10.3390/foods10030687
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Dehydration Temperature Modulates the Transcriptomic Programme and Flavonoid Profile of Grape Berries

Abstract: Raisins are a popular and nutritious snack that is produced through the dehydration of postharvest grape berries under high temperature (HT). However, the response of the endogenous metabolism of white grape varieties to postharvest dehydration under different temperature have not been fully elucidated to date. In this study, the white grape cultivar ‘Xiangfei’ was chosen to investigate the effect of dehydration at 50 °C, 40 °C, and 30 °C on the transcriptomic programme and metabolite profiles of grape berries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The same effect was observed in color with higher values of the colour change (ΔE) in samples subjected to prolonged temperature exposure (9.3 vs 5.3 at 50 °C/360 min and 60 °C/300 min, respectively). In the same way, Chen et al (2021) found that the combination of high temperatures/low times (50 °C for 5 days vs 40 °C for 12 days and 30 °C for 30 days) favoured the accumulation of glucose, fructose and total soluble sugars and the contents of citric acid, lactic acid, malic acid, tartaric acid, and gallic acid and its derivatives in grape berries.…”
Section: Dehydration Methodsmentioning
confidence: 62%
See 4 more Smart Citations
“…The same effect was observed in color with higher values of the colour change (ΔE) in samples subjected to prolonged temperature exposure (9.3 vs 5.3 at 50 °C/360 min and 60 °C/300 min, respectively). In the same way, Chen et al (2021) found that the combination of high temperatures/low times (50 °C for 5 days vs 40 °C for 12 days and 30 °C for 30 days) favoured the accumulation of glucose, fructose and total soluble sugars and the contents of citric acid, lactic acid, malic acid, tartaric acid, and gallic acid and its derivatives in grape berries.…”
Section: Dehydration Methodsmentioning
confidence: 62%
“… High temperatures favoured the accumulation of some phenols (mainly gallic acid and its derivatives), while the highest accumulation of flavonoids and proanthocyanidins was achieved when lower temperatures were used. Chen et al (2021) Strawberry Convective drying (50 °C and 60 °C, 1.5 m/s) ΔE was greater in strawberries dried longer (9.3 vs 5.3 for 50 °C and 60 °C, respectively). Higher loss of TPC (60.9 % vs 78.1 % for 60 °C and 50 °C, respectively) andanthocyanins (45 % vs 26 % for 60 °C and 50 °C, respectively) with temperature.…”
Section: Effect Of Dehydration On Berries Quality Bioactive Compounds...mentioning
confidence: 86%
See 3 more Smart Citations